Dinophysis, a highly specialized mixoplanktonic protist - Reguera, Beatriz; García-Portela, María; Velasco-Senovilla, Esther; Rial, Pilar; Escalera, Laura; Díaz, Patricio A.; Rodríguez, Francisco (Frontiers in Protistology, 2024)
Several Dinophysis species produce lipophilic toxins (diarrhetic shellfish poisoning, DSP and pectenotoxins PTX) which are transferred through the food web. Even at low cell densities (< 10 3 cell L -1 ), they can cause human illness and shellfish harvesting bans; toxins released into the water may kill early life stages of marine organisms. Dinophysis species are mixotrophs: they combine phototrophy (by means of kleptoplastids stolen from their prey) with highly selective phagotrophy of the ciliate Mesodinium, also a mixotroph which requires cryptophyte prey of the Teleaulax/Geminigera clade. Life cycle strategies, biological interactions and plastid acquisition and functioning in Dinophysis species make them exemplars of resilient holoplanktonic mixoplankters and of ongoing speciation and plastidial evolution. Nevertheless, 17 years after the first successful culture was established, the difficulties in isolating and establishing cultures with local ciliate prey, the lack of robust molecular markers for species discrimination, and the patchy distribution of low-density populations in thin layers, hinder physiological experiments to obtain biological measurements of their populations and slow down potential advances with next-generation technologies. The Omic's age in Dinophysis research has only just started, but increased efforts need to be invested in systematic studies of plastidic diversity and culture establishment of ciliate and cryptophyte co-occuring with Dinophysis in the same planktonic assemblages.